Portable Moving Images : a Media History of Storage Formats - Cedeño Montaña, Ricardo (De Gruyter, 2017)
This media history explores a series of portable small cameras, playback devices, and storage units that have made the production of film and video available to everyone. Covering several storage formats from 8mm films of the 1900s, through the analogue videotapes of the 1970s, to the compression algorithms of the 2000s, this work examines the effects that the shrinkage of complex machines, media formats, and processing operations has had on the dissemination of moving images. Using an archaeological approach to technical standards of media, the author provides a genealogy of portable storage formats for film, analog video, and digitally encoded video. This book is a step forward in decoding the storage media formats, which up to now have been the domain of highly specialised technicians.